Penerapan Metode SAS dapat Mengatasi Kesulitan Membaca Permulaaan pada Siswa Kelas II SD GMIH Sopi Kecamatan Morotai Jaya Kabupaten Pulau Morotai - Rima Sumahi; M. Rais Salim; Julia Ismali (Peneliti.net, 2021)
Beginning reading skills in grade II students at SD GMIH Sopi are not considered optimal. This is caused by several factors, one of which is the concept of learning that is less attractive, because the teacher is less precise in choosing and implementing effective reading methods. The media used is also not varied. The results of this study indicate that the improvement of the initial reading process through the SAS method is related to student activities, namely the ability of students to decipher simple sentences into letters and arrange letters into simple sentences. Students are more active and enthusiastic in participating in learning to read beginning with the application of the SAS method so that the ability to read at the beginning of grade II students at SD GMIH Sopi can increase.